ANALISIS DISTRIBUSI KLOROFIL, NITROGEN, DAN KARAKTERISTIK DAUN SALAK SIDIMPUAN (Salacca sumatrana Becc.) BERDASARKAN POSISI DAUN DI KECAMATAN ANGKOLA BARAT - Jumaria Nasution; Suswati; Syahbudin Hasibuan (Universitas Nias Raya, 2026)
Sidimpuan salak (Salacca sumatrana Becc.) is a leading horticultural commodity in the Tapanuli region and is commonly cultivated under natural agroforestry systems beneath tree canopies. Leaf chlorophyll and nitrogen contents are important indicators of photosynthetic capacity and plant nutritional status, and their values may vary according to leaf position. This study aimed to analyze the distribution of chlorophyll, nitrogen, and leaf morphological characteristics of Sidimpuan salak based on leaf position (basal, middle, and apical) across three villages at different elevations, namely Sibakua Village (approximately 674 m above sea level), Hutakoje Village (approximately 550 m above sea level), and Sigumuru Village (approximately 470 m above sea level) in South Tapanuli Regency, North Sumatra, Indonesia. A total of 20 sample plants were selected from each location using purposive sampling. Chlorophyll and nitrogen contents were measured using a SPAD meter at the three leaf positions, while leaf area was calculated using the formula L = l × w × k (k = 0.7), where l represents leaf length and w represents leaf width. The data were analyzed using two-way analysis of variance (ANOVA), followed by Duncan's Multiple Range Test (DMRT). Location and leaf position had highly significant effects (p < 0.01) on chlorophyll and nitrogen contents, whereas their interaction was not significant. The highest chlorophyll and nitrogen contents were observed at the basal leaf position and gradually decreased toward the leaf apex. Among the study locations, the highest chlorophyll and nitrogen contents were recorded in Sigumuru, while the lowest values were found in Hutakoje. In contrast, the largest leaf area was observed in Hutakoje. The basal leaf position is therefore recommended as the most representative sampling position for assessing the chlorophyll and nitrogen status of Sidimpuan salak plants.